2021
DOI: 10.21037/apm-21-37
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative treatment compliance, anxiety and depression of elderly patients with ophthalmic surgery and the influential factors

Abstract: Background: Ophthalmic surgery is invasive, and treatment efficacy is affected by a variety of factors. We aimed to analyze perioperative treatment compliance, anxiety and depression of elderly patients undergoing ophthalmic surgery and the influential factors. Methods:The study group comprised 119 elderly patients undergoing ophthalmic surgery between March 2018 and March 2020. Clinical and treatment compliance data of all patients were collected. The self-rating anxiety scale (SAS) and self-rating depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Invasive surgery can easily induce a stress response, mainly manifested as excessive expression of inflammatory factors[ 19 ]. On the one hand, the production of large amounts of inflammatory cells can increase the incidence of postoperative infection; on the other hand, it can directly affect the surgical outcome[ 20 ]. IL-6 and TNF-α are typical pro-inflammatory factors, which are important mediators that trigger and initiate inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive surgery can easily induce a stress response, mainly manifested as excessive expression of inflammatory factors[ 19 ]. On the one hand, the production of large amounts of inflammatory cells can increase the incidence of postoperative infection; on the other hand, it can directly affect the surgical outcome[ 20 ]. IL-6 and TNF-α are typical pro-inflammatory factors, which are important mediators that trigger and initiate inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis, atopic dermatitis, acne, steroid-dependent dermatitis, and alopecia have a certain impact on the life quality of most patients, and may cause different degrees of anxiety and depression. In recent years, emerging research has shown that the skin is not only a target for the regulation of psychological stress signals, but is also actively involved in the local hypothalamus-pituitary-adrenal (HPA) axis, peripheral nerve terminals as well as stress responses and immune cells including keratin-forming cells, mast cells and skin cells ( 15 - 17 ).…”
Section: Introductionmentioning
confidence: 99%